COSMIC REVELATIONS: UNLOCKING THE SECRETS OF THE UNIVERSE - Akabirova, Kamola Malikovna; Shodmonov, Jurabek Isokul ugli (Educational Research in Universal Sciences, 2023)
This passage explores the fascination and complexity of the universe, tracing humanity’s historical curiosity through ancestral imaginations to modern scientific theories. It discusses celestial phenomena, dark matter, and introduces key theories such as the Big Bang and the speculative Big Bounce Theory. The narrative navigates through astrophysical concepts like ultra-massive black holes and cosmic voids, highlighting advancements in observation technologies such as telescopes and surveys.